1987
DOI: 10.3109/00498258709167412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biliary excretion on the disposition of felodipine and metabolites in the rat

Abstract: 1. After i.v. and intraduodenal administration of 3H-felodipine to rats, approx. 50% of the dose was excreted in bile in the first 6 h. Total urinary and biliary recoveries after both administration routes were similar. 2. Neither unchanged felodipine nor oxidized pyridine metabolite was detected in bile. Bile collection had no effect on the blood concentration-time profiles of either compound. 3. Bile collection decreased the area under the blood concentration-time curve (AUC) of total, unidentified felodipin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It has been shown that compounds with molecular weights between 350 and 450 can be extensively eliminated by the rat both in urine and bile [12], whereas the molecular weight threshold for biliary secretion may be higher in humans [13]. The behaviour of felodipine metabolites seems to correspond to this guideline, as studies in bile duct-cannulated rats showed that 50% of a single IV dose of [3H[felodipine was secreted as metabolites in bile in the first 6 h after dosing [3].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It has been shown that compounds with molecular weights between 350 and 450 can be extensively eliminated by the rat both in urine and bile [12], whereas the molecular weight threshold for biliary secretion may be higher in humans [13]. The behaviour of felodipine metabolites seems to correspond to this guideline, as studies in bile duct-cannulated rats showed that 50% of a single IV dose of [3H[felodipine was secreted as metabolites in bile in the first 6 h after dosing [3].…”
Section: Discussionmentioning
confidence: 98%
“…A. Sutfin et al: Biliary secretion of felodipine metabolites dose was secreted in bile, since the major proportion secreted by that route in the rat appeared there during the first 4-5 h after dosing [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations